2010
DOI: 10.1007/s12646-010-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Life events stress and chronic pain

Abstract: Stress in life has been found to play a role in triggering, maintaining and exacerbating chronic pain, yet, direct empirical evidence of the mechanism of such a role is limited. In the present study 120 non-selected chronic pain patients and an equal number of matched healthy normals were investigated with regard to life events stress. The investigation revealed that although, patients and controls did not differ in terms of number of events experienced during the last 1 year, however, patients reported signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Employment issues while working with chronic pain provided more life stress for those with FM compared to healthy controls in terms of trouble with bosses and/or major changes in working hours/conditions. This has also been reported elsewhere [ 25 ]. Moreover, Palstam and Mannerkorpi [ 44 ] conducted a systematic review of both quantitative and qualitative studies on employment in those with FM and found that certain working conditions contributed to higher rates of disability in this group.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Employment issues while working with chronic pain provided more life stress for those with FM compared to healthy controls in terms of trouble with bosses and/or major changes in working hours/conditions. This has also been reported elsewhere [ 25 ]. Moreover, Palstam and Mannerkorpi [ 44 ] conducted a systematic review of both quantitative and qualitative studies on employment in those with FM and found that certain working conditions contributed to higher rates of disability in this group.…”
Section: Discussionsupporting
confidence: 89%
“…Despite small numbers, certain environmental factors were particularly stressful for individuals with FM in our study (changes in eating habits, declines in sleep quality, the death of a close friend, employment issues), consistent with prior research in individuals with chronic pain. For example, diet and eating behaviors were reported as stressful events for FM individuals in our study, in concert with [ 25 , 32 ]. Seib and colleagues [ 32 ] also found that sleep disturbances were related to increased stress, more depression, and lower quality of life in those with chronic pain; see also [ 25 ].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations